The reality of academic accreditation in Saudi universities in light of accreditation experiences in the United States of America & Japan and the United Kingdom - Al-Mutair, Ebtesam Abdulrahman; Al-Rshoud, Hend Abdulrahman; Al-Juffair, Haya Abdulrahman; Al-Tuwaijri, Fatima Abdulaziz (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to identify the reality of the institutional academic accreditation of Saudi universities in the light of the experiences of some countries, and to achieve this goal the comparative descriptive approach was used to describe the actual reality of academic accreditation in the following four comparison countries Saudi Arabia, the United States of America, Japan and the United Kingdom, in terms of the supervisors of academic accreditation, academic accreditation standards, and academic accreditation procedures, and then to analyze the similarities and differences between them.The study found that there was a significant similarity between the four countries in accreditation objectives and some accreditation criteria and accreditation procedures, and differed in the number of accreditation institutions. In light of this, some benefits have been extracted to develop the institutional academic accreditation of Saudi universities. The researchers also made a number of recommendations and proposals to raise the standards of academic accreditation in the kingdom's universities to meet their counterparts in the comparison countries.
Keywords: Academic accreditation; Saudi universities; higher education; institutional accreditation